Sistem Penjaminan Mutu Internal dalam Peningkatan Mutu Hasil Pendidikan di Universitas Islam Nusantara Bandung - R Supyan Sauri; Ayi Nazmul Hidayat; Deti Rostini (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
The purpose of this study is to describe the implementation of the Internal Quality Assurance System in Improving the Quality of Education services at Uninus as an effort to improve the quality of inputs, processes, and output outcomes. This is very important considering the quality of study program performance issues are so complex from the start of student input, teaching and learning processes, fulfillment of graduation standards, infrastructure and human resources. Other problems in the management of study programs have not been optimal implementation of higher education quality standards both academic and non-academic. This study uses a qualitative research approach, with the case study method. Research activities carried out at the Directorate of Quality Assurance, Quality Assurance Group, Quality Assurance Unit and Study Programs at Uninus Graduate School. How to collect data through observation, documentation and in-depth interviews with data sources and informants. The results illustrate (a) There are policies and SPMI concepts, in the form of academic quality standard documents and non-academic quality standard documents that are formulated and determined by the Directorate of Quality Assurance as a reference in implementing the Directorate General of Higher Education quality standards in the Study Program, coordinating with the Quality Assurance Group and the Unit Quality Assurance for setting standards, implementing standards, evaluating standards, controlling standards and improving quality standards in the study program; (b) The internal quality assurance system is implemented through the stages of planning, implementation and evaluation of the SPMI cycle; (c) barriers to implementation include commitment by the leadership is not optimal, the number of personal auditors is limited, SPMI is implemented only when facing accreditation. (d) The solution is to anticipate obstacles in the form of providing experts in SPMI implementation, training for young auditors, fostering quality assurance spirit, carry out evaluation in every semester. Utilization of SPMI evaluation results in the context of building a quality culture, enhancing the BAN-PT accreditation rating and gratification to customers.